Public Relations Communication Adaptation in Islamic University Branding for Gen Z - Rasuli, Rasuli; Utari, Prahastiwi; Sudarmo, Sudarmo (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2025)
This study explores how the Public Relations Division of Universitas Muhammadiyah Surakarta, as an Islamic higher education institution, adapts its branding messages on social media to reach and build a positive image among Gene Z. The study focuses on the BHP UMS , internal stakeholders, and an analysis of UMS’s social media content from January 2023 to May 2025. The method employed is a case study with a qualitative descriptive approach. The findings reveal that UMS Public Relations adapts the university’s branding messages through strategies involving content, symbols, language, and formats that align with the characteristics and trends of Gen Z, without neglecting institutional values rooted in Al-Islam and Kemuhammadiyahan. This contributes to UMS’s positive image. These findings have significant implications for strengthening Public Relations’ communication adaptation strategies in university branding toward Gen Z, without disregarding institutional values.